The many sides of land tenure - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Land Tenure in Development Cooperation: Guiding principles. GTZ no. 264. 1998. 252 pp ISBN 3 88085 521 8 Deutsche Gezellschaft für Technische Zusammenarbeit Postfach 5180 65726 Eschborn, Germany Fax: + 49 6196 79 1115